Past, Present and Future of Language Education - Komorowska, Hanna (Glottodidactica, 2013)
The article analyses main issues in the present-day SLA and FLT against the background of those aspects of the past of language education which are not particularly well covered by group memory. Emphasis is given to parts forgotten and reinvented, ideas distorted and fields revisited. An attempt is made to examine the role of past and present in shaping the outline of future trends in language policy, language teaching and teacher education.